2013
DOI: 10.1186/1472-6955-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of case studies in undergraduate didactic nursing courses: a qualitative study

Abstract: BackgroundThe implementation of unfolding scenario-based case studies in the didactic classroom is associated with learner-centered education. The utilization of learner-centered pedagogies, such as case studies, removes the focus from the instructor and instead places it on the student. Learner-centered pedagogies are believed to improve students’ levels of cognition. The purpose of this study was to examine how nurse educators are implementing the pedagogies of case studies in their undergraduate didactic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…Nursing students have suggested that unfolding case studies enhanced their critical thinking skills and problem-solving abilities (Day, 2011;Dutra, 2013;Himes & Ravert, 2012;Page, Kowlowitz, & Alden, 2010;Popil, 2011;Yousey, 2013), increased their collaboration and teamwork (Forneris et al, 2012), and offered preparatory guidance into their professional nurse role (Bennett et al, 2011;Himes & Ravert, 2012;Lewenson & Truglio-Londrigan, 2013;West et al, 2012). In addition, an increase in student engagement (Dutra; Popil), satisfaction, and self-esteem (Himes & Ravert, 2012;Mills et al, 2014) was noted as a result of exposure to unfolding case studies.…”
Section: Review Of Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…Nursing students have suggested that unfolding case studies enhanced their critical thinking skills and problem-solving abilities (Day, 2011;Dutra, 2013;Himes & Ravert, 2012;Page, Kowlowitz, & Alden, 2010;Popil, 2011;Yousey, 2013), increased their collaboration and teamwork (Forneris et al, 2012), and offered preparatory guidance into their professional nurse role (Bennett et al, 2011;Himes & Ravert, 2012;Lewenson & Truglio-Londrigan, 2013;West et al, 2012). In addition, an increase in student engagement (Dutra; Popil), satisfaction, and self-esteem (Himes & Ravert, 2012;Mills et al, 2014) was noted as a result of exposure to unfolding case studies.…”
Section: Review Of Literaturementioning
confidence: 94%
“…Unfolding case studies have been used within simulation experiences (Filer, Champlin, & Hunt, 2012;Johnson et al, 2012;McCormick, Slavy, & Fuller, 2013;Mills et al, 2014), as an on-line component (Anderson, Page, & Wendorf, 2013;Bennett, Kennedy, & Donato, 2011;Johnson & Flagler, 2013;Lewenson & Truglio-Londrigan, 2013;Yousey, 2013), and within didactic courses (Dudas, 2012;Dutra, 2013;West, Usher, & Delaney, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Consistent with the call that nurses must achieve a higher level of education and training (National Academy of Sciences, Committee on the Robert Wood Johnson Foundation Initiative on the Future of Nursing, at the Institute of Medicine, ), case studies have been explored and utilized in teaching nursing students (Dutra, ; Grossman et al., ; Majeed, ; Swanson et al., ). Grossman et al.…”
Section: Discussionmentioning
confidence: 99%
“…This participatory teaching method engages students in active and reflective learning. Case studies have been shown to facilitate collaborative learning through discussion and collective problem solving (Hofsten, Gustafsson, & Haggstrom, ) and have been used in nursing education (Dutra, ; Grossman et al., ). Swanson et al.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Therefore, case studies were developed to serve as a teaching and learning strategy to translate theoretical knowledge (peer-reviewed articles and content from the vodcast) into clinical practice in a safe environment. Case studies as an experiential learning experience [15][16][17] provide an opportunity to mimic real-world practice by articulating underlying principles of safe, competent, and ethical nursing practice (developing a critical thinking pathway) which is one of the main premises of introducing case studies as a teaching and learning strategy in nursing education. [17] These strategies may address the struggle between the enormity of content required and the application of this knowledge to facilitate transformational learning for the nursing student's current clinical practicums and future nursing practice.…”
Section: Design Of Classmentioning
confidence: 99%